Costs of Adverse Event Management Associated with First-Line Cetuximab or Panitumumab in Metastatic Colorectal Cancer Patients in Saudi Arabia - Gihan Elsisi; Hana Abdul Kareem; Abdelaziz Alaseiri; Abdullah Alsharm; Mohammed Algarni; Hajer Al-Mudaiheem; Fouad Alnagar; Hazem Lotfy; Mohamed Ouda; Ahmed Elshehri (Journal of Health Economics and Outcomes Research)
# Introduction In Saudi Arabia, patients with metastatic colorectal cancer (mCRC) with wild-type RAS mutations may be treated with either cetuximab plus chemotherapy (CET + CT) or panitumumab plus chemotherapy (PAN + CT), which are epidermal growth factor receptor (EGFR) antibodies. This study calculated the costs of adverse event (AE) management linked to anti-EGFR treatment in Saudi Arabia’s national health budget from payer and societal perspectives.